KNOWLEDGE IN THE FIELD OF KNOWLEDGE ENGINEERING AND MANAGEMENT (Perspectivas em Ciência da Informação, 2010)
There is a diversity of interpretations for the concepts of terms like "information" and "knowledge", suggesting the ideas of value of information and value of knowledge, that covering their merely structural characteristics. This hinders the understanding and acceptance of new areas of studies, such as, the area of Knowledge Engineering and Management. Through the revision of part of that theoretical diversity and their critics, this text proposes the inclusion and the expansion of the term "cognition" as a necessary factor to differentiate between "information" and "knowledge", in the field of Knowledge Engineering and Management. Besides, some implications of this epistemological positioning are shown through a revision in the processes of conversion of the knowledge, presented by Nonaka and Takeuchi (1997), and in the knowledge level modelling, proposed by Allen Newell (1981).